Stable thin‐wire model of buried pipe‐type power distribution cables for 3D FDTD transient simulation. Issue 25 (7th December 2020) - Li, Binghao; Ding, Yuxuan; Du, Yaping; Chen, Mingli
Abstract : Underground cables such as pipe‐type cables are widely used in urban power industry. In this study, an advanced thin‐wire model of the pipe‐type cables is 3D FDTD simulations. In this model, the multi‐conductor cables are represented with two‐level transmission line equations. A stabilising technique with a 1D spatial low‐pass filter is proposed to maintain computational stability. Frequency‐dependent losses are fully considered by using a vector‐fitting technique. The proposed thin‐wire model is validated with the multi‐conductor transmission line theory analytically and the traditional FDTD method numerically. Good agreements are observed. It is found that the simulation maintains stability for 360, 000‐time steps. Compared to the traditional FDTD method, the memory space and computation time of the proposed model can be reduced by 73% and 98%, respectively. Induced lightning currents in a cable connection station are analysed. It is found that, without considering soil ionisation and soil stratification, the peak current in the metallic armour is 1.54 times as much as the one with considering these non‐linear effects. It can be reduced by 9.04% and 18.6% if the cable is buried at depths of 1 m and 1.5 m, compared with the case of a 0.5 m buried depth.